A fertilidade do conceito de professor-pesquisador a partir do desenvolvimento do estágio vinculado à pesquisa - Almeida, Whasgthon Aguiar de (2008)
This is a research study based on a theoretical perspective, epistemologically as a tool for analysis of a pedagogical practices for teacher-researchers on a course for graduation. Discusses the process of training of teacher-researcher from the development of a practical stage bound for the search. Want to investigate to what extent a process of probation tied to the research contributes to the legitimacy of identity in teaching and promoting professional autonomy / intellectual of the teacher to the Teaching of Science. Aims to: investigate how the process of probation tied to the research helps in the training of teacher-researcher of the field in order to legitimize their identity to awake from his teaching and professional autonomy / intellectual. It also aims to discuss the interface between the Philosophy of Science and scientific research from the process of historical development in research in the West, reflect on the need for education to act as articulating science of science education to consolidate the stage tied to search, view the theoretical nuances that characterize the epistemology of the teacher-researcher demonstrating how they can sustain their professional autonomy / intellectual identity and its teaching; describe the process of probationary teacher's showing of the field as his relationship with the research contributes to the Science Education teacher. Guided to a qualitative approach focused on action research using the techniques of participant observation and semi-structured interview. Reflects on the various dimensions of the concept of research and training related to the teaching process. Initially shows the picture of modern science commenting on the epistemology of theorists who have contributed to its consolidation. Supports the need to treat education as a science education aimed at legitimizing a process of Science Education toward the training of teachers. Sets out the definitions and distinctions made by theoreticians who study the Teaching of Science, Education and Scientific Literacy for Scientific then suggest a perspective that envisages the training of teacher-researcher. It proposes that the elements characteristic of teacher training, such as: identity, knowledge, independence and professionalism are treated as concepts that underpin the prospect of Science Education. It develops an idea that the stage is also tied to search is a process of Science Education focused on teacher training may help in re of their teaching practices from their own experiences in the classroom. With this, believes that the teacher will object to the subject of knowledge, and able to deconstruct it and rebuild it. In this context, describes a process of stage toward the training of teacher-researcher, developed in the field of education, showing the steps of her life and methodological systematising the data obtained during the investigation. Aiming to offer subsidies that enable the creation of strategies and methodologies for the training of teacher-researcher is presented as a product of research on the structure of a methodological model of the elements that characterized the research.